2004
DOI: 10.4025/actascianimsci.v26i3.1836
|View full text |Cite
|
Sign up to set email alerts
|

Influência das adubações nitrogenada e fosfatada sobre a produção e características da rebrota do capim Marandu (Brachiaria brizantha (Hochst) Stapf cv. Marandu)

Abstract: RESUMO. O objetivo foi avaliar o efeito da adubação nitrogenada e fosfatada sobre o vigor da rebrota (VR), perfilhamento, produção de massa seca total (MSVT) e massa seca verde de lâmina foliar (MSVLF), sob níveis de nitrogênio (0; 200; 400; 600kg/ha de N) e de fósforo (0; 50; 100; 150; 200Kg/ha de P2O5) do capim Marandu (Brachiaria brizantha (Hochst) Stapf cv. Marandu), no período de verão (PV) e inverno (PI). Utilizou-se um delineamento experimental de blocos casualizados, fatorial 4 x 5 com três repetições.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 2 publications
0
7
2
13
Order By: Relevance
“…According to the authors, this significant effect is due to the fact that the P content in soil before the experiment deployment was very low (2.1 mg dm -3 of P), thus easier crop response to the application of phosphate fertilizers of higher solubility, according to Oliveira et al (2012) that found higher DMY due to use of simple superphosphate, compared to Arad phosphate. Cecato et al (2000), working with N rates (0, 200, 400 and 600 kg ha -1 of N) and P rates (0, 50, 100, 150 and 200 kg ha -1 of P2O5) in Marandu palisadegrass observed significant positive effect of P doses in the production of total dry matter, however, this increase in production was only 5%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the authors, this significant effect is due to the fact that the P content in soil before the experiment deployment was very low (2.1 mg dm -3 of P), thus easier crop response to the application of phosphate fertilizers of higher solubility, according to Oliveira et al (2012) that found higher DMY due to use of simple superphosphate, compared to Arad phosphate. Cecato et al (2000), working with N rates (0, 200, 400 and 600 kg ha -1 of N) and P rates (0, 50, 100, 150 and 200 kg ha -1 of P2O5) in Marandu palisadegrass observed significant positive effect of P doses in the production of total dry matter, however, this increase in production was only 5%.…”
Section: Resultsmentioning
confidence: 97%
“…According to Cecato et al (2000), P has several benefits for forage plants, as conditioning roots and seedlings to more quickly development, and to improve efficiency in water use. P is important for enhancing forage nutritional value, as it influences in plant height, according to Bennett et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…continuação Maior interferência das plantas daninhas, nos manejos de fertilidade do solo estudados, foi causada no solo com adição de silicato de cálcio e magnésio e adubação pelo convívio do milho com U. brizantha e I. grandifolia, com redução média de 59% no acúmulo de N em relação à cultura (Tabela 3). Assim como no milho, o N é o principal macronutriente limitante na produtividade das pastagens, principalmente aquelas formadas por espécies do gênero Urochloa (CECATO et al, 2004). Portanto, conforme constatado por Rajcan e Swanton (2001), a presença de um competidor durante o desenvolvimento e crescimento inicial do milho pode alterar a disponibilidade de N no solo e sua distribuição na planta.…”
Section: Resultsunclassified
“…No primeiro ano, a aplicação de 112,5 m³ ha -1 proporcionou uma produtividade de 2334 kg ha -1 . No segundo ano, a produtividade da pastagem teve menor ganho por m³ de dejeto aplicado em relação ao primeiro ano (p < 0,05), por causa do efeito do dejeto ser apenas residual, com acúmulos de 7,56 kg ha A adubação nitrogenada favoreceu o acúmulo de maior quantidade de massa seca de forragem (SANTOS et al, 2009;BENETT et al, 2008;CECATO et al, 2000), comprovando o potencial do dejeto como fonte de nutrientes. Em estudos realizados por YOLCU et al (2010), não foram revelados aumentos de produtividade da massa seca em forragem, quando utilizado apenas o esterco bovino na forma líquida; porém, a combinação de estercos líquido e sólido teve efeitos positivos na produtividade.…”
Section: Introductionunclassified